2015
DOI: 10.1002/hed.23604
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/PTEN/AKT/mTOR polymorphisms: Association with clinical outcome in patients with head and neck squamous cell carcinoma receiving cetuximab‐docetaxel

Abstract: We identified combined genotypes associated with outcome of HNSCC, which might have an impact for identification of a target population for cetuximab-docetaxel treatment. Results should be considered as an initial finding and warrant validation in larger clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 34 publications
0
24
0
2
Order By: Relevance
“…The AKT family (AKT1-3) has been found to integrate extracellular signals in several cellular processes, including growth, proliferation, differentiation, migration and survival (28). Numerous studies have demonstrated that the phosphoinositide 3-kinase (PI3K)/AKT/mammalian target of rapamycin pathway serves an essential role in apoptosis and is frequently activated in numerous types of human cancer, such as head and neck squamous cell carcinoma (29,30), prostate cancer (31), breast cancer (32) and colorectal cancer (33). Cancer cells have a higher proliferation rate compared with wild-type cells and frequently lose the ability to undergo apoptosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…The AKT family (AKT1-3) has been found to integrate extracellular signals in several cellular processes, including growth, proliferation, differentiation, migration and survival (28). Numerous studies have demonstrated that the phosphoinositide 3-kinase (PI3K)/AKT/mammalian target of rapamycin pathway serves an essential role in apoptosis and is frequently activated in numerous types of human cancer, such as head and neck squamous cell carcinoma (29,30), prostate cancer (31), breast cancer (32) and colorectal cancer (33). Cancer cells have a higher proliferation rate compared with wild-type cells and frequently lose the ability to undergo apoptosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that single mutations in the PI3K pathway may be responsible for SCCHN formation whereas multiple mutations in the pathway components cause disease progression. Indeed, a recent Phase II study determined whether genetic variations in the genes for PIK3CA, PTEN, AKT1, AKT2, and FRAP1 (mTOR) were associated with differences in disease progression, survival, and response to therapy in a cohort of patients with recurrent and/or metastatic SCCHN treated with docetaxel plus cetuximab [42]. They demonstrated a correlation between the single-nucleotide polymorphisms PTEN:rs12569998 and AKT2:rs8100018 and risk of progression and PFS.…”
Section: The Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Pfisterer K et al . revealed that patients with variants of AKT2:rs8100018 had a higher risk of progression after docetaxel and cetuximab and experienced a shorter progression-free survival in squamous cell carcinomas of the head and neck 42 . However, in contrast to these results, our study found that patients with AKT2:rs8100018 variants had a lower risk of recurrence after receiving preoperative CRT followed by radical surgery and experienced a longer DFS.…”
Section: Discussionmentioning
confidence: 99%